Arabic Vehicle Licence Plate Recognition Using Deep Learning Methods: Review - Alkawsi G.; Baashar Y.; Alkahtani A.A.; Kiong T.S.; Habeeb D.; Aliubari A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Automatic vehicle identification; Automation; Deep learning; Optical character recognition; Arabic characters; Artificial intelligent; Deep learning; Identification accuracy; Learning approach; Learning methods; Learning techniques; Middle East; Performance; Vehicle license plate recognition; License plates (automobile)